Forum Wahana Lingkungan Hidup Indonesia (Walhi) Lampung dalam Kasus Revisi Perda RZWP3K Berdasarkan Perspektif Advocacy Coalition Framework - Khairunnisa Maulida (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
Revision of Regional Regulation number 1 of 2018 which contains a zoning plan for coastal areas and small islands in each province which is considered to be able to castrate a lot of living space in coastal communities in several islands. This situation can be read in regional regulation number 1 of 2018 which divides each settlement of fishermen into an area of ??11.66 hectares. WALHI Lampung, which is an environmental forum with 14 other memberships, gave a form of rejection and then cancellation of the revised regional regulation on RZWP3K in other words, namely zoning regulations. The purpose of writing is to identify and explain the Lampung Walhi Forum in the case of rejecting the revision of the Regional Regulation RZWP3K based on the perspective of the Advocacy Coalition Framework (ACF). The results of the study There are two coalitions in the revised Perda RZWP3K, where each individual carries the logic of belief systems, namely coalitions A and B where both coalitions have differences in the framework of the ACF approach. The value system in the case of the revised Perda RZWP3K based on the ACF perspective is in the form of a political interest system of the Lampung Provincial Government included in the regional legislative program of the Lampung Provincial DPRD or in the ACF study it is called the Core believe system. The civil society coalition in the case of the rejection of the revised Perda RZWP3K was formed on the basis of the same vision, namely rejecting the revision of the Perda RZWP3K. The decision of the Lampung Provincial DPRD in revising the Law made the Lampung Civil Society Coalition reject the regulation which is currently included in the 2020 Lampung Province legislation program.